Perancangan dan Implementasi Sistem Ticketing Support untuk Pengelolaan Pengaduan Pelanggan - Affi Himmawan; Nur Wakhidah (Jurnal Teknologi Informasi dan Multimedia, 2026)
CV. Metamorphz Technology Solutions is a company operating in the information technology sector that receives various complaints and service requests from customers in its daily opera-tions. Previously, the customer complaint management process was carried out manually, causing inefficiencies in recording, tracking, and resolving complaint tickets. This condition resulted in slow customer response times and difficulty in monitoring complaint status in realtime. This study aims to implement support ticketing system to manage customer complaints at CV. Meta-morphz Technology Solutions. The research method used is the Agile Development method, which consists of five stages: requirements analysis, system design, implementation, testing, and maintenance. The system was developed using a web-based platform with a SQL Server data-base, equipped with a chatbot feature based on a Natural Language Processing (NLP) algorithm using a Rule-Based and TF-IDF (Term Frequency-Inverse Document Frequency) approach for au-tomatic classification and matching of complaint categories. The chatbot acts as the first line of customer interaction in receiving, classifying, and providing initial responses to complaints before forwarding them to the relevant technical team. The results show that the ticketing sys-tem integrated with the chatbot successfully streamlines the complaint handling process, enabling structured complaint recording, automated ticket assignment to the relevant technical team, and realtime monitoring of complaint status. System testing using the Black-Box Testing method showed that all system features function according to requirements, with a test success rate of 100% from nine testing scenarios conducted. The implementation of this ticketing system im-proves response time and service quality to customers, as well as facilitating performance moni-toring of the technical support team.